2013
DOI: 10.1159/000353281
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-G and Regulatory T Cells during Specific Immunotherapy for Pollen Allergy

Abstract: Background: TH2-biased immune responses are important in allergy pathogenesis. Mechanisms of allergen-specific immunotherapy (SIT) might include the induction of regulatory T cells (Tregs) and immunoglobulin (Ig) G4 blocking antibodies, a reduction in the number of effector cells, and skewing of the cytokine profile towards a TH1-polarized immune response. We investigated the effects of SIT on T cells, on immunomodulation of human leukocyte antigen (HLA)-G, which has been assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…When considering allergic diseases, elevated levels of sHLA-G molecules have been detected in plasma and bronchoalveolar lavage fluid of atopic asthmatics [42][43][44][45] and in plasma from AR patients, where their levels correlated with clinical severity and response to pharmacological therapy [48,49]. Of interest, specific immunotherapy is able to reduce the sHLA-G antigen levels in serum [50] and in the supernatant from PBMCs stimulated in vitro with allergen [47]. More recently, it has been reported that patients with seasonal allergic rhinitis had significantly higher sHLA-G serum levels than patients with perennial allergic rhinitis [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering allergic diseases, elevated levels of sHLA-G molecules have been detected in plasma and bronchoalveolar lavage fluid of atopic asthmatics [42][43][44][45] and in plasma from AR patients, where their levels correlated with clinical severity and response to pharmacological therapy [48,49]. Of interest, specific immunotherapy is able to reduce the sHLA-G antigen levels in serum [50] and in the supernatant from PBMCs stimulated in vitro with allergen [47]. More recently, it has been reported that patients with seasonal allergic rhinitis had significantly higher sHLA-G serum levels than patients with perennial allergic rhinitis [52].…”
Section: Discussionmentioning
confidence: 99%
“…ported that elevated levels of sHLA-G molecules are detected in plasma and bronchoalveolar lavage fluid of atopic asthmatics [42][43][44][45], that the production of sHLA-G in unstimulated PBMC cultures is significantly higher in subjects with occupational isocyanate-induced asthma as compared with asymptomatic-exposed controls [46] and that the amount of sHLA-G detected in the medium from PBMC stimulated with allergen in vitro is reduced after specific immunotherapy [47]. Moreover, previous studies in allergic rhinitis (AR) patients indicated that sHLA-G serum levels were: i) significantly increased in comparison with normal subjects; ii) elevated both outside and during the pollen season in patients with seasonal allergy; and iii) correlated with clinical severity, drug use, allergen-specific IgE levels, type of allergy and response to immunotherapy [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of sHLA-G in culture supernatants confirmed that high amounts of sHLA-G molecules are found when the causal allergen is used as stimulus. Soluble molecules detected in culture supernatants mainly belong to the HLA-G5 isoform suggesting that they are actively secreted by immune cells after incubation with allergen ( 69 , 70 ).…”
Section: In Vitro Datamentioning
confidence: 99%
“…Some years ago, Tregs appeared to be a good marker for such assessment. In many studies, clinically successful ASIT went together with increased proportion of Tregs, increased population of IL-10 + cells, and/or hypomethylation of forkhead box P3 (Foxp3) (Fujimura et al 2011 ; Lou et al 2012 ; Scadding et al 2010 ; Sørensen et al 2013 ; Suárez-Fueyo et al 2014 ; Swamy et al 2012 ; Syed et al 2014 ). However, other authors did not demonstrate any alterations in the number of Tregs after ASIT (Kim et al 2011 ; Lou et al 2012 ; Moed et al 2013 ; Schubert et al 2009 ; Stelmaszczyk-Emmel et al 2015 ; Thunberg et al 2010 ).…”
Section: Regulation Of Immune Response In Allergymentioning
confidence: 99%